A psychological approach in the usage of interests to motivate children to the learning of EFL in a public school of Nuevo León, Mexico - Trejo Robles, Cathy Elizabeth (2019)
The present work focuses on 10-year-old children from a public school of Nuevo León, Mexico that have difficulties in the learning of English as a Foreign Language (EFL) and making lesson plans’ adaptations including the students’ interests. The general objective is to examine the relationship between interests and learning of children who show difficulties in the learning process of EFL. The participants in this study are 29 children from a 5th grade primary public school who study English, 2 selected students, one English instructor and one practitioner researcher. The instruments used are based on the concept of triangulation, and the data collection tools are observation forms, interviews, questionnaires about interests and student work. Data analysis from a questionnaire about interests was performed and the main interest categories found were physical activities and videogames. These categories are considered as the thematic content to be used in order to adapt the lesson plans of the EFL classes. The conclusions from the analysis of the students' behaviors and participation during the EFL classes are that the students did not show an improvement during the first class even though it included elements of interest to them, but that changed in the second and third classes. In a scale from 0 to 20 points, it can be observed quantitatively that S1 incremented his participation from 8 in the first class to 15 in the third class, and S2 also incremented his participation from 12 in the first class to 17 in the third class.